Respostas
respondido por:
6
3x-13=11
3x=11+13
3x=24
x=24/3
x= 8
9y+20=5y+4
9y-5y=4-20
4y= -16
y= -16/4
y= -4
3x=11+13
3x=24
x=24/3
x= 8
9y+20=5y+4
9y-5y=4-20
4y= -16
y= -16/4
y= -4
respondido por:
4
3x -13 = 11
3x = 11 + 13
3x = 24
x= 24/3
x =8
9y + 20 = 5y + 4 leva o 5y p/ primeiro membro com sinal trocado.
9y - 5y = -20 +4 troca de membro também troca o sinal.
4y = -16
y = -16/4
y = -4
3x = 11 + 13
3x = 24
x= 24/3
x =8
9y + 20 = 5y + 4 leva o 5y p/ primeiro membro com sinal trocado.
9y - 5y = -20 +4 troca de membro também troca o sinal.
4y = -16
y = -16/4
y = -4
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás